Analisis Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT Taqwa Mulia Wisata - Atina Hasanatain; Dian Marlina Verawati (Universitas Muhammadiyah Sumatera Utara, 2022)
An important element in improving employee performance is the role of leaders in the company so that they can manage the mindset of human resources so that they can obey and carry out every job in accordance with company expectations. Transformational leadership style is a leadership style that prioritizes the value of the leader in producing a vision, mission and environment that motivates employees to achieve beyond their expectations (Burns in Dewi, 20212). Work motivation is also one of the factors that influence employee performance improvement by providing motivation and encouragement to employees to be able to produce maximum performance. The purpose of this study was to determine whether there was a significant effect between transformational leadership style and work motivation on employee performance at PT Taqwa Mulia Wisata. The sampling technique in this study used purposive sampling totaling 31 people. This study uses a quantitative method with a multiple linear regression approach and the analytical tool used is SPSS software, the results of the data taken show an R Square of 0.581, which can be concluded that the influence of transformational leadership style and work motivation simultaneously affects employee performance is 58 ,1%.